Implementing Business and Human Rights for Sustainable Development under Nigeria’s Domestic Legal Regime - Salawu, Busari Morufu (Dhaka University Law Journal, 2025)
Protecting business and human rights in Nigeria is challenging in view of the national insecurity and violence. The study undertook an overview the United Nations’ Guiding Principles on Business and Human Rights. It examined the legal regime of business and human rights under Nigerian domestic laws. It also identified and appraised challenges to the implication of the UNBHR in Nigeria. The study adopted a doctrinal method, adopting primary and secondary sources of information. The primary source comprised the Constitution of the Federal Republic of Nigeria 1999, Arbitration Act 2004; Nigeria Export Import Promotion Act 2004, Labour Act 2004, Trade Disputes Act 2004 to mention a few and the case law. The secondary source included textbooks, journal articles, conference proceedings, newspapers, and the internet. The study found that the UNGP are comprehensive and protect business and human rights of persons, corporate bodies, and the government. Findings further revealed that the domestic laws in Nigeria handshake the UNBHR because their provisions are adequate and suficient to protect business and human rights. There are legal and institutional challenges to the full implementation of UNBHR due to weak implementation of domestic laws, rule of law, pervasive corruption, ignorance, unemployment, and poverty. The paper concluded with a recommendation that for business and human rights to be protected, sustainable battles must be fought against corruption, poverty and insecurity to promote good governance. Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 249-270